The Educational Management Guidelines by using a Community Participation Process for a Child Development Center in Phadungmart Sub-district, Janae district, Narathiwat Province - Kanyati, Kanokwan; Choosuwan, Recha (Asia Social Issues, 2021)
The purpose of this research was to study the guidelines of educational management by using a community participation process in a Childhood Development Center in Phadungmart Sub-district, Janae District, Narathiwat Province. This study used qualitative research that was designed for this specific research. There were 40 participants who were considered key informants to the research. This group included 10 representatives of the Child Development Center Committee, 9 teachers, children’s parents, and community leaders. A purposive sampling was used to select the participants. Semi-structured interviews were used to collect as much in-depth data as possible. The data was analyzed by a content analysis technique. The research findings revealed that the guidelines of educational management in this particular study refer to principles and methods of educational management in accordance with the Child Development Center operating standards. There are 6 principles which are listed here. (1) Decentralization of educational administration by participation of communities from all regions. There are 4 areas in which these methods are used. The first is that of participation in making decisions and planning, determining measures, and creating guidelines for educational management. The second area is defining various department systems. The third area is establishing a community representative committee. And the final area is the presentation of information (2) Participation in the development of the potential of community personnel. This involves training methods such as career skills seminars, personnel education development and building morale in people. The second evaluation of performance is by making a policy plan and checking the implementation of project activities. (3) Cooperative management based on mutual trust. There are 2 methods that are used to assess development and system security. (4) Integrating knowledge management from communities. There are 3 methods that search for learning resources and local wisdom, planning meetings for integration of local knowledge and wisdom and procuring community folk philosophers. (5) Positive empowerment of the community by creating an understanding of the operations of the Child Development Center by using project presentations and inviting community members to join activities of the Child Development Center. The purpose of these activities would be to develop leaders and create engaging forums where all groups can share their ideas. And (6) Principles of empowerment from a network outside the Child Development Center by building an attitude of confidence in the Child Development Center. Establishing a parent network can help reach these goals as well as promote and support the development of networks in the community.